Kajian Hukum Pengaturan Pemanfaatan Ruang Bawah Tanah - Arbianzah, Mahendra Tio (WARKAT, 2024)
This study examines the inconsistencies between Government Regulation No. 18/2021 and the Basic Agrarian Law regarding the concept of land rights and the utilization of underground space. The aim is to review the juridical aspects of the regulation of underground space utilization and the implications of the inconsistency. Using conceptual and statutory approaches, as well as systematic and grammatical interpretation, this research analyzes land rights theories from various experts to examine aspects of ownership and control of underground space. The results show that there are inconsistencies between PP No. 18/2021 and UUPA and Law No. 26/2007 in regulating the utilization of underground space. There is a difference in principle between the UUPA, which integrates land rights with underground space, and the Job Creation Law, which separates the two. This research analyzes the concept of "Underground Space Use Rights" and "Underground Space Unit Rights" as new legal instruments to accommodate underground space utilization. In conclusion, a comprehensive legal framework is needed that regulates aspects of access, development, utilization, and ownership of buildings in underground space in a harmonious manner by taking into account the principles of legal certainty, justice, and expediency.